Family Dynamics May Influence an Individual’s Substance Use Abstinence Self-Efficacy - Ram, Daphna (J Addict Prev Med, 2016)
BACKGROUND: Previous work on substance use suggests the influence of family dynamics on emotion regulation. OBJECTIVE: The present study examined the role of family in substance use recovery. It is of importance to examine whether conflict with various family members influences an individual’s abstinence self-efficacy. METHODS: We examined individual abstinence self-efficacy scores and lifetime conflict with mother, father, and siblings in a sample of 200 women who had been justice involved. RESULTS: We found that conflict with mother was the best predictor of abstinence self-efficacy compared to conflict with father and conflict with siblings. Individuals who indicated having conflict with mother over their lifetime had lower confidence that they could abstain from use in potentially emotionally triggering situations. CONCLUSIONS/IMPORTANCE: These findings suggest that family dynamics, specifically lifetime conflict with mother, do play a role in an individual’s confidence to regulate emotions in high-risk relapse situations without turning to substances. Limitations include using abstinence self-efficacy as a proxy for emotion regulation and not directly measuring emotion regulation. Examining family relationships may be especially important in the treatment of women in recovery from substance use.